Expectation-maximization algorithm for amplitude estimation of saturated optical transient signals - Kagie, Matthew J; Lanterman, Aaron D (Journal of the Optical Society of America. A, Optics, image science, and vision, 2018)
This paper addresses parameter estimation for an optical transient signal when the received data has been right-censored. We develop an expectation-maximization (EM) algorithm to estimate the amplitude of a Poisson intensity with a known shape in the presence of additive background counts, where the measurements are subject to saturation effects. We compare the results of our algorithm with those of an EM algorithm that is unaware of the censoring.